Ergometric principles of cardiovascular function assessment in arterial hypertension - A. V. Bursikov; E. Sh. Valiulina; L. N. Birtseva (Кардиоваскулярная терапия и профилактика, 2011)
Aim. To investigate hemodynamic and ergometric parameters and their agreement with metabolic demand during veloergometry in patients with Stage I-II arterial hypertension (AH). Material and methods. In total, 80 18-59-year-old men, with Stage I-II AH were examined, together with 25 healthy men of comparable body weight. All participants underwent standard veloergometry, with achievement of sub-maximal heart rate (HR), or development of test-termination criteria, such as excess blood pressure (BP) elevation, dyspnoea, or fatigue. Results. A significant increase in myocardial oxygen consumption, disagreeing with metabolic demand, was observed both at rest and during veloergometry test. The qualitative criteria reflecting myocardial workload due to peripheral vascular resistance and functional myocardial remodelling were developed. These criteria differed at different AH stages, and included hemodynamic parameters (levels of systolic and diastolic BP) and ergometric characteristics (double product and its increase, pressure load index, and cardiac load index). Conclusion. In Stage I-II AH patients, myocardial oxygen consumption during standard veloergometry was significantly higher than in healthy individuals, disagreed with metabolic demand, and increased with AH progression.